2001
DOI: 10.1097/00005392-200105000-00044
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of the Efficiency of Early Postoperative Bladder Emptying After the Stamey Procedure or Pubovaginal Sling for Stress Urinary Incontinence

Abstract: These data show that early postoperative voiding dysfunction, measured using bladder emptying efficiency, after the pubovaginal sling is no more common than after the Stamey procedure and help justify the broadened indications for pubovaginal sling for treatment of stress urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Moreover, in a study by Wang and Chen [14], nearly 45% of patients were unable to leak urine during a cough test in the dorsal lithotomy position. As there is no exact method of determining how much tension to put on the sling during surgery, the surgeon must rely chiefly on experience to make the judgement [3,4]. However, we found that patients with ISD were unlikely to achieve early efficient emptying and thus would not be suitable for discharge as day‐cases.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Moreover, in a study by Wang and Chen [14], nearly 45% of patients were unable to leak urine during a cough test in the dorsal lithotomy position. As there is no exact method of determining how much tension to put on the sling during surgery, the surgeon must rely chiefly on experience to make the judgement [3,4]. However, we found that patients with ISD were unlikely to achieve early efficient emptying and thus would not be suitable for discharge as day‐cases.…”
Section: Discussionmentioning
confidence: 96%
“…The EE was calculated as VV/(VV + PVR) × 100. Efficient emptying was defined as an EE of ≥ 75%[3]. Patients were considered suitable for discharge from hospital when emptying efficiently or when they could use CISC confidently with adequate pain control and had no significant complications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation